Gender, Conversion, and the End of Empire in the Teaching of Jacob, Newly Baptized - Jacobs, Andrew S. (Journal of early Christian studies, 2021)
The seventh-century apocalyptic dialogue text Doctrina Jacobi nuper baptizati ("Teaching of Jacob, Newly Baptized") depicts forcibly baptized Jews coming to terms with their new situation in hidden meetings led by Jacob. At a key moment in the text, the last voices of Jewish resistance belong to the wife and mother-in-law of one of the dialogue participants. This essay uses this moment of Jewish women's resistance to interrogate the gendered nature of conversion and empire in the Doctrina Jacobi; the faith of converts and the power of empire are both feminized in such a way as to dislocate orthodoxy from empire and promote a masculinized, non-Jewish, post-Roman eschaton. Although the text is often read as a defense of imperially forced baptism, the situation of the baptized Jews remains tenuous and ambiguous, as does the power of the empire that baptized them. The baptized Jews, always incomplete, never quite reaching full Christianity, become the sad mascots of imperial failure, while orthodox Christians imagine their own triumphant future. Nonetheless, I suggest, the ambiguities of this Christian imaginary create a space for future Jews forced into baptism to imagine their own forms of resistance from the margins. [End Page 93]